Philosophy of the Act and the Pragmatics of Fiction. - Wood, Tahir (Cambridge Scholars Publisher, 2021)
This is a ground-breaking work that offers a new explanation of the power and popularity of literary fictional texts. It does this by explaining the multiple dimensions of any fictional text and why it is that fictional literature cannot be reduced to a subset of these dimensions. This book offers an expansion of the field of pragmatics, ""the philosophy of the act, "" in which the three categories of fictional actors--author, character and reader--can be given their due. It achieves this by bringing together schools of thought that are too often kept apart: Anglo-American pragmatics and Europe